Integration In the Curriculum of Teaching the Arabic Language (In Terms of Goals and Materials) - Baiq Tuhfatul Unsi (Journal of Arabic Language Teaching, 2021)
Integration is a method of organizing the elements of the language experience given to students and teaching them by balancing and connecting all language skills to achieve the expected goal of students mastering and understanding language from all sides, both linguistic and language skills. Darus Salam Boarding School Jombang is one of the institutions that use an integrative curriculum, which is a curriculum that combines modern and traditional boarding School curriculum. By implementing the integration curriculum, graduates can speak Arabic well and understand Arabic books well. This study aims to analyze the integration of the Arabic learning curriculum in Darus Salam Boarding School Jombang in terms of objectives and materials. Researchers used a qualitative approach to case studies. Researchers use the method of collecting data from observations, interviews, and documents. Then analyze the data using Miles and Huberman's analysis theory by collecting, sorting, and presenting it; the researcher uses data triangulation, theory triangulation, and expert triangulation. The result of this research is that the integration in terms of the objective aspect is the integration between the mastery of productive and receptive language skills, and the integration of the material element is the integration between linguistic and religious materials. التكامل أسلوب لتنظيم عناصر الخبرة اللغوية المقدمة للطلاب، وتدريسها بما يحقق ترابطها وتوحدها بجميع المهارات اللغوية لتحقيق الأهدف المنشودة ، أي أن يتقن الطلاب اللغة ويفهمونها من جميع الجوانب ، اللغويات والمهارات اللغوية. معهد دار السلام جومبانج من إحدى المعاهد التي استخدم إدارة التعليم التكاملي، يعني يُعمل في معهد دار السلام المنهج التكاملي، حيث الجمع بين المنهج العصري والسلفي. وبالتكامل يقدر الطلاب على تكلم باللغة العربية تكلما جيدا وفهم نصوص المكتوبة فهما جيدا. وأراد هذا البحث لتحليل نموذج التكامل في مناهج تعليم اللغة العربية بمعهد دار السلام جومبانج من جانب الأهداف والمواد. استخدمت الباحثة المدخل الكيفي بالدراسة الحالة. واستخدمت الباحثة طريقة جمع البيانات من الملاحظة والمقابلة والوثائق. ثم تحليل البيانات باستخدام نظرية مايليس وهيبيرمان بطريقة جمع البيانات، فرزها وعرضها.واستخدمت الباحثة التثليث بالبيانات، التثليث بالنظرية، والتثليث بالخبراء. النتيجة من هذا البحث هي: إن التكامل في ناحية الأهداف هو التكامل الذي دمج بين إتقان مهارة اللغوية الانتاجية و الاستقبالية، و التكامل في ناحية المواد هو التكامل الذي دمج بين المواد التعليمية اللغوية و المواد الدينية.